Gnathostomiasis: an emerging infectious disease relevant to all dermatologists - Francisco Bravo; Bernardo Gontijo (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Gnathostomiasis is a parasitic infection caused by the third larval stage of nematodes of the genus Gnathostoma. The disease is endemic in some countries around the world. In the American continent, the majority of cases is concentrated in Mexico, Ecuador, and Peru. However, due to increasing traveling either at the intercontinental or intracontinental level, the disease is seen each time more frequently in tourists. Furthermore, countries, such as Brazil, that have never been considered endemic are reporting autochthonous cases. The disease usually presents as a deep-seated or slightly superficial migratory nodule in patients with history of eating raw fish, in the form of ceviche, sushi, or sashimi. Along with the clinical presentation, diagnostic criteria include either blood or tissue eosinophilia. In most instances, these criteria are enough for the attending physician to institute therapy. Chances of finding the parasite are low, unless the biopsy is taken from a very specific area that develops after antiparasitic treatment is started. The potential of other organ involvement with more serious consequences should always be kept in mind.